2017
DOI: 10.1088/1475-7516/2017/08/027
|View full text |Cite
|
Sign up to set email alerts
|

De Sitter and scaling solutions in a higher-order modified teleparallel theory

Abstract: The existence and the stability conditions for some exact relativistic solutions of special interest are studied in a higher-order modified teleparallel gravitational theory. The theory with the use of a Lagrange multiplier is equivalent with that of General Relativity with a minimally coupled noncanonical field. The conditions for the existence of de Sitter solutions and ideal gas solutions in the case of vacuum are studied as also the stability criteria. Furthermore, in the presence of matter the behaviour o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 96 publications
2
94
0
Order By: Relevance
“…In [25,37] the authors found that there is one extra gravitational polarization mode in this theory, as in f (R) gravity. It has been found that f (T, B) cosmology can explain dark energy without evoking a cosmological constant and also that this theory can describe a transition from a matter dominated era to two different accelerated eras, one of which describes a de Sitter universe [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In [25,37] the authors found that there is one extra gravitational polarization mode in this theory, as in f (R) gravity. It has been found that f (T, B) cosmology can explain dark energy without evoking a cosmological constant and also that this theory can describe a transition from a matter dominated era to two different accelerated eras, one of which describes a de Sitter universe [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the non-holonomic frame is inherent in the structure of spacetime we have at our disposal n 2 new parameters h µ i which can be used for the definition of dark energy. We associate with dark energy the scalar field of geometric origin and noncanonical kinetic term with energy momentum tensor [45,46]…”
Section: Field Equationsmentioning
confidence: 99%
“…In this article, we work in the context of the TEGR by considering a higher-order theory of gravity which introduces a scalar field with a noncanonical kinetic term as a dark-energy component [45,46] 1 . Another well-known scalar field which is related with a modified theory is the field in the O'Hanlon theory which describes the geometrodynamic degrees of freedom in f (R) −gravity.…”
Section: Introductionmentioning
confidence: 99%
“…If we replace the above equation and also use the Friedmann constraint (63), the remaining three Eqs. (48), (53) and (54) gives us the following set of equations,…”
Section: B Flat Flrw Cosmologymentioning
confidence: 99%